2014
DOI: 10.1158/1078-0432.ccr-13-1683
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-Dependent Protein Kinase II and Its Endogenous Inhibitor α in Medullary Thyroid Cancer

Abstract: Purpose: Calcium/calmodulin-dependent kinase II (CaMKII) is involved in the regulation of cell proliferation. Its endogenous inhibitor (hCaKIINa) is expressed in some cell types. We determined the role of CaMKII in RET-stimulated proliferation and hCaMKIINa in medullary thyroid carcinoma (MTC).Experimental Design: We analyzed the role of RET mutants on CaMKII activation in NIH3T3 and in MTC cell lines, and determined the effect of CaMKII inhibition on RET/ERK pathway and cell proliferation. Then the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…ERK is one of the targets of CaMKII and the CaMKII-ERK cascade has been identified in a recent study (19). Furthermore, a previous study demonstrated that the CaMKII-mediated activation of ERK contributed to cell proliferation of papillary thyroid carcinoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…ERK is one of the targets of CaMKII and the CaMKII-ERK cascade has been identified in a recent study (19). Furthermore, a previous study demonstrated that the CaMKII-mediated activation of ERK contributed to cell proliferation of papillary thyroid carcinoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the physiological inhibitor-α of CaMK-II in primary medullary thyroid carcinoma cells inversely correlates with the capacity to form lymph node metastasis [234]. In human follicular thyroid cancer cells Ca 2+ entry via TRPC1 (transient receptor potential channel 1) appears to be important for migration and invasiveness.…”
Section: Cam-dependent Protein Kinasesmentioning
confidence: 99%
“…32 Using RT-PCR (reverse transcription polymerase chain reaction) confirmed that no mRNA of the blocked calmodulin was transcribed after application of RNAi. The activated calmodulin was found to stimulate an adenylyl cyclase as indicated by inhibitor studies with indomethacine as well as several calmodulin blockers 37 all of which block gravitaxis in Euglena . In contrast, forskulin activates the adenylyl cyclase 38 and augments gravitaxis.…”
Section: Introductionmentioning
confidence: 99%